Telecom Branding in Pakistan: Network Coverage or Value Added Services - Kamran Ahmed Siddiqui; Mazhar Ali; Irshad Hussain Sarki; Rafique Ahmed Khuhro (Academic Journal of Research in Economics and Management, 2015)
Purpose - This study explores the factors of telecom branding in Pakistan. Design/methodology/approach - Survey methodology was used to collect the data and a total of 238 mobile phone users were interviewed for their telecom brand preferences. Findings - Exploratory factor analyses and cross tabulations were used to measure the results, four major antecedents were extracted, Brand Association, Brand Premium, Brand Communication and Brand Loyalty. Cross tabs show wider differences in male and female customers for their perceptions towards bases of telecom branding. Secondly, three factors were identified as shaping the telecom branding i.e. Network coverage, Value added services and Pricing strategies while in subsequent quests value added services were emerged as major factor for retaining consumer mindset for telecom branding. Research limitations/implications - A few strengths of social research; the universal use of self-reporting questionnaires, and use of students in the research process, which make the process robust and economically feasible, are actually highly criticized in different nonacademic quarters. Practical implications - The findings point to various implications for practicing managers especially those who are responsible for segmentation, targeting and positioning their services. Originality/value - Although there are many studies on brand preferences; research on telecom brand antecedents is very limited. This research adds significant value by dissemination of knowledge on the subject area.
Keywords: 330; Telecom; Mobile Phone; Services; Branding; Marketing; Pakistan